KEPUASAN DAN LOYALITAS KONSUMEN PADA ONLINE MARKET DI INDONESIA - F. Alia Humarah (Jurnal Manajemen dan Pemasaran Jasa, 2013)
The goal of this research activity is to investigate what things will improve consumer satisfaction and loyalty of online stores in Indonesia. Researchers can take advantage of the results obtained and then menginformasikannya and giving knowledge to the company so they know what things need to be improved and safeguarded against consumers shop online; as well as prevent things which will reduce consumer satisfaction. The findings in this study indicate that there is a positive influence a) adaptation (adaptation), (b) interaction (interactivity), (c) maintenance (nurturing), (d) commitment (commitment), (e) network (network), (f) diversity (assortment), (g)the ease of transaction (transaction ease), and (h) the agreement of usage(engagement) towards customer satisfaction, there is a positive influence customer satisfaction to customer loyalty, there is a positive influence of Inertia, of the relationship between customer satisfaction and customer loyalty, and there is a positive influence Trust affect the relationship between customer satisfaction to customer loyalty The result of this research has implications for the business online, to increase the satisfaction and loyalty of customers on the company maintains, secondly, to academics who want to develop a theory that advanced. Recommendations for further research are expected to be able to use the online shop globally as a comparison object of research, the addition of other variables also affect customer satisfaction and loyalty in the online market.Keyword: Customer Satisfaction, Loyalty and Online Market